Learning Applications World Map for Primary Schools using Macromedia Flash MX - Andanu Budi Prakasa (Jurnal Sistem Informasi, 2008)
The development of computerized technology in the education world increasingly fast. Even the education-education in our country are also taking a computer as one part of the lessons learned. With this method the computer approach to the children who performed early, and by taking the material they learn in the education-education in their schools, children can recognize and understand the computer further. As capital for them to face the times.